Effect of platelet-derived β-thromboglobulins on coagulation. Issue 154 (June 2017) - Egan, Karl; van Geffen, Johanna P.; Ma, Hui; Kevane, Barry; Lennon, Aine; Allen, Seamus; Neary, Elaine; Parsons, Martin; Maguire, Patricia; Wynne, Kieran; O' Kennedy, Richard; Heemskerk, Johan W.M.; et al.
Abstract: Background: β-thromboglobulins are derived from the cleavage of the CXC chemokine platelet basic protein and are released in high concentrations by activated platelets. Platelet-derived β-thromboglobulins (βTG) share 70% homology with platelet factor 4 (PF4), another CXC chemokine released by activated platelets. PF4 modulates coagulation by inhibiting heparin-antithrombin interactions, promoting protein C activation, and attenuating the activity of activated protein C. In contrast, the effect of βTG on coagulation is unknown. Aim/Methods: Clotting times, thrombin generation, chromogenic clotting factor assays, and surface plasmon resonance (SPR) were used to assess the effect of purified βTG on coagulation. Results: In normal pooled plasma, βTG shortened the lagtime and time to peak thrombin generation of tissue factor (TF)-dependent and TF-independent thrombin generation. In factor VIII and factor IX-deficient plasmas, βTG induced thrombin generation in the absence of a TF stimulus and in the presence of anti-TF and factor VIIa inhibitory antibodies. The procoagulant effect was not observed when thrombin generation was independent of factor X activation (supplementation of factor X-deficient plasma with factor Xa). Cleavage of a factor Xa-specific chromogenic substrate was observed when βTG was incubated with factor X, suggesting a direct interaction between βTG and factor X. Using SPR, βTG were found to bind to immobilised factor X in a dose dependent manner. Conclusion: βTG modulate coagulation in vitro via an interaction with factor X. Graphical abstract: Highlights: The effect of platelet derived β-thromboglobulins on coagulation was assessed. Platelet-derived β-thromboglobulins increase the rate of thrombin generation. Platelet-derived β-thromboglobulins interact with coagulation factor X.